2006
DOI: 10.1002/pat.676
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, swelling behaviors and application of polyacrylamide/attapulgite superabsorbent composites

Abstract: A series of superabsorbent composites, polyacrylamide/attapulgite (PAMA), were prepared from acrylamide (AM) and attapulgite micropowder in aqueous solution, using N,N 0 -methylenebisacrylamide (MBA) as a crosslinker and ammonium persulfate (APS) as an initiator and then saponified with sodium hydroxide solution. This paper focuses on swelling behaviors of the PAMA superabsorbent composites in various saline solutions. The results indicate that saline solutions can weaken the swelling abilities of the PAMA com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 20 publications
5
25
0
Order By: Relevance
“…Na + has no effect on -COO À and -CONH 2 groups, and the decrease of water absorbency for PAAm composite is mainly due to the decrease of osmotic pressure and the screening effect. These results are all consistent with the decreasing of water absorbency for PAAm composite and the corresponding interpretation reported elsewhere [28]. The well-known relationship between the swelling and salt solution concentration is stated in Eq.…”
Section: Effect Of Ion Strengthsupporting
confidence: 93%
“…Na + has no effect on -COO À and -CONH 2 groups, and the decrease of water absorbency for PAAm composite is mainly due to the decrease of osmotic pressure and the screening effect. These results are all consistent with the decreasing of water absorbency for PAAm composite and the corresponding interpretation reported elsewhere [28]. The well-known relationship between the swelling and salt solution concentration is stated in Eq.…”
Section: Effect Of Ion Strengthsupporting
confidence: 93%
“…It can be seen from the Fig. that the water absorbency decreases with increasing ionic strength of NaCl solution as reported by other works . It is caused by the reduction of the osmotic pressure between sample and external swelling medium.…”
Section: Resultssupporting
confidence: 80%
“…Conversely, the hydration radius of various cations increase as follows: K + , NH 4 + , Na + , Ba 2+ , Ca 2+ , Mg 2+ , Al 3+ . The cation with small hydration radius has high charge density, which gives an evident screening effect on the anionic groups of polymer chains, and leads to low equilibrium water absorbency . In addition, for eliminating the effect of ionic strength on equilibrium water absorbency, all solutions were adjusted to the same ionic strength.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…This will also decrease the water absorbency for both hydrogel specimens. [52,53] Figure 6(b) displays the effect of dose on swelling (%) of hydrogel specimens from different contents of PLAA inside hydrogel structures. Generally, it was observed that by increasing exposure radiation dose, the swelling of gel decreases.…”
Section: Network Studiesmentioning
confidence: 99%